2016
DOI: 10.1016/j.enbuild.2015.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Balancing daylight, glare, and energy-efficiency goals: An evaluation of exterior coplanar shading systems using complex fenestration modeling tools

Abstract: Exterior shades are the most effective way to control solar load in buildings. Twelve different coplanar shades with different geometry, material properties and cutoff angles were investigated for two California climates: the moderate San Francisco Bay Area climate and a hot and dry Southern California climate. The presented results distinguish themselves from other simulation studies by a newly developed method that combines three research-grade software programs (Radiance, EnergyPlus and Window 7) to calcula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(23 citation statements)
references
References 7 publications
0
19
0
Order By: Relevance
“…In order to achieve a balance between spatial contrast and light level. So, a balance between outside view, glare probability, spatial contrast, light level and concentration level on tasting and chatting [39].…”
Section: Discussionmentioning
confidence: 99%
“…In order to achieve a balance between spatial contrast and light level. So, a balance between outside view, glare probability, spatial contrast, light level and concentration level on tasting and chatting [39].…”
Section: Discussionmentioning
confidence: 99%
“…Coplanar shading systems have been analysed by Hoffman in Ref. [9] developing a complex fenestration system not only for daylighting analysis but also for distributing the solar loads on the surfaces of internal environments. The authors found that the paradigm of reducing window to wall ratio for reducing cooling loads could be relaxed employing shading devices.…”
Section: Introductionmentioning
confidence: 99%
“…in offices. Yet the supply of daylight and a view to the outside are essential performance criteria in facade design since they address energy efficiency targets as well as the comfort and well-being of occupants [2,3].…”
Section: Background and Objectivesmentioning
confidence: 99%